(untitled) (Research, Society and Development, 2023)
Odontoma is the most common type of odontogenic tumor, it usually forms in the jaws during tooth development, being classified into compound and complex odontoma. Complex odontoma occurs more frequently in lower molars, mostly causing impaction of permanent elements, and can be discovered by an investigative action originating from non-eruption of teeth, radiographic examinations or by edema, pain, trismus resulting from an odontogenic infection. Objective: This work consists of demonstrating a clinical case of complex infected odontoma in a young male patient. As a conduct, a surgical treatment was chosen, removing the entire tumor and the dental element 27 that was impacted and with torn roots, the diagnostic hypothesis was confirmed, and the surgery eliminated the focus of infection, generating the resolution of the case. Final considerations: Cases of erupting and infected odontomas are rare, and when they occur they cause great discomfort to the patient, and the surgeon must have a quick and resolving surgical action, in view of being in an emergency situation.